An Intra-Abdominal Pseudocyst around a Ventriculoperitoneal Shunt due to Streptococcus Infection 7 Years after Shunt Surgery. (5th January 2014) - Tomiyama, Arata; Harashina, Jun-ichi; Kimura, Hitoshi; Ito, Keisuke; Honda, Yoshihiko; Yanai, Hiroyuki; Iwabuchi, Satoshi
Abstract : In 1999, a 50-year-old woman underwent ventriculoperitoneal (VP) shunt surgery for hydrocephalus after subarachnoid hemorrhage. She was hospitalized for fever and recurrent systemic seizures in November 2006. Head computed tomography (CT) showed only old changes. The seizures and fever were controlled by medicinal therapy. However, in December, her consciousness level suddenly decreased, and she showed progressive lower abdominal distension. Head CT showed marked ventriculomegaly, and abdominal CT showed a giant cystic mass at the shunt-tube tip in the lower abdominal cavity. Because thick pus was aspirated from the intra-abdominal mass, we diagnosed the patient with acute obstructive hydrocephalus due to an infected abdominal pseudocyst. Laparotomy and direct cyst drainage were performed, and antibiotic therapy against Streptococcus, the causative pathogen, was administered. The VP shunt tube was replaced. The postoperative course was uneventful, and postoperative CT showed hydrocephalus improvement and no pseudocyst recurrence. Abdominal pseudocysts, which are rare after VP shunt surgeries, usually occur after the subacute postoperative course in younger cerebral hemorrhagic cases. Our case was quite rare because the cyst developed in the chronic phase in an older patient and was caused by streptococcal infection. The cyst components should be examined before cyst drainage when choosing surgical strategies.